2020
DOI: 10.14744/nci.2020.57767
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland tumors: a 15-year experience of a universıty hospital in Turkey

Abstract: T he salivary glands consist of three major glands as parotid, submandibular and sublingual glands and hundreds of minor glands, which are diffusely located in the beginning part of the respiratory system. Tumors of the salivary glands are rarely encountered. However, they appear with different histopathological characters. Different biological behaviors can be observed even in neoplasms defined by the same name. In the latest classification made by the World Health Organization (WHO) in 2017, salivary gland t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(103 reference statements)
1
4
0
3
Order By: Relevance
“…It was found that the pleomorphic adenoma was the most frequent type of salivary gland tumor, accounting for 53.4% of all tumors and 69.6% of benign tumors. Other studies involving tumors of salivary glands reported similar results, with pleomorphic adenoma representing the most frequent tumor type 8,15,[19][20][21][22][24][25][26][27][28][29]31,[34][35][36] and commonly found on the right side. Interestingly, this distribution was observed in the parotid tumors evaluated.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It was found that the pleomorphic adenoma was the most frequent type of salivary gland tumor, accounting for 53.4% of all tumors and 69.6% of benign tumors. Other studies involving tumors of salivary glands reported similar results, with pleomorphic adenoma representing the most frequent tumor type 8,15,[19][20][21][22][24][25][26][27][28][29]31,[34][35][36] and commonly found on the right side. Interestingly, this distribution was observed in the parotid tumors evaluated.…”
Section: Discussionsupporting
confidence: 62%
“…Cy s t i c a d e n o i d c a rc i n o m a w a s t h e m o s t prevalent malignant salivary gland tumor (6 cases), representing 8.2% of all tumors and 35.3% of malignant tumors, compatible with what was found in other studies 12,14,15,17,20,22,24,28,30,34 . However, the mucoepidermoid carcinoma, another malignant tumor, was the most prevalent 8,12,14,21,31,35,36 in other studies. Mucoepidermoid carcinoma and adenocarcinoma not otherwise specified (NOS) after cystic adenoid carcinoma, were the second most common tumors found.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…El adenocarcinoma de células claras de glándulas salivares menores representa el 1% de los tumores malignos de glándulas salivales. De hecho, en revisiones de casos, como la de Mengi et al, con 366 casos de tumores de glándulas salivales, no se hace referencia a adenocarcinomas de células claras de glándula salival menor [7]. Silva Cunha et al [8], con 164 casos reportados de tumores de glándulas salivales, tampoco reporta casos de adenocarcinomas de células claras de glándula salival menor; así mismo en la publicación de Gonzales et al [9],con 107 casos de tumores de glándulas salivales.…”
Section: Discussionunclassified
“…En la literatura se menciona el diagnóstico diferencial con oncocytoma, carcinomas mioepiteliales, metástasis de tumor renal, entre las más citadas por los diferentes artículos revisados. En cuanto al pronóstico es bueno en la mayoría de casos reportados en la literatura internacional, pero se debe hacer hincapié en que el número de casos de esta patología es reducido [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionunclassified